Origanum dubium (Cypriot Oregano) as a Promising Sanitizing Agent against Salmonella enterica and Listeria monocytogenes on Tomato and Cucumber Fruits - Xylia, Panayiota; Chrysargyris, Antonios; Miltiadous, Panagiota; Tzortzakis, Nikos G. (My University, 2022)
In recent years, the use of natural products such as essential oils (EOs) and other plant extracts for the preservation of fresh produce has attracted much interest from the food industry. Many endemic medicinal and aromatic plants, such as Cypriot oregano (Origanum dubium), present a plethora of properties that can be utilized by the fruit and vegetable sectors of the food industry. The purpose of the present study was to assess the effects of O. dubium EO and hydrosol (at different concentrations and durations of dipping application) for the preservation of tomato and cucumber fruit quality, and their effectiveness as sanitizing agents against two foodborne pathogens (Listeria monocytogenes and Salmonella enterica). The results of this study indicated that increased concentrations of EO, combined with a longer duration of application, resulted in less marketable fruit compared to hydrosol application. Interestingly, EO application at lower concentrations and shorter durations of application (i.e., 0.01% for 5 min) increased fruit antioxidant, ascorbic acid and carotenoid levels (for tomato fruit), suggesting an increase in the nutritional value of the treated fruit, compared to the control. EO and hydrosol were able to decrease the bacterial populations (both bacteria) on fruits. Both products were especially effective against L. monocytogenes, even seven days after their application and storage at 11 °C (up to an approx. 3 log reduction with the EO application). Overall, the results of this study suggest that the use of O. dubium EO and hydrosol could be considered as alternative sanitation means for tomatoes and cucumbers.
Keywords: tomato; Origanum dubium; cucumber; food safety; fresh produce quality; sanitizing agents